Genetic structure of wild rice Zizania latifolia in an expansive heterogeneous landscape along a latitudinal gradient - Wagutu, Godfrey Kinyori; Fan, Xiangrong; Fu, Wenlong; Tengwer, Miriam Chepkwemoi; Li, Wei; Chen, Yuanyuan (Frontiers in Ecology and Evolution, 2022)
Global aquatic habitats are undergoing rapid degradation and fragmentation as a result of climate change and changes in land-use. Understanding the genetic variability and adaptive potential of aquatic plant species is thus important for conservation purposes. In this study, we investigated the genetic diversity and structure of the extant natural populations of Zizania latifolia from five river basins in China based on 46 microsatellite markers. We tested isolation by environment (IBE), isolation by resistance (IBR) and isolation by distance (IBD) patterns using a reciprocal causal model (RCM). Furthermore, the impact of environment on Z. latifolia genetic diversity was elucidated using generalized linear models and spatially explicit mixed models. Low genetic diversity (HE = 0.125–0.433) and high genetic differentiation (FST = 0.641, Øpt = 0.654) were found. Higher historical gene flow (MH=0.212–2.354) than contemporary gene flow (MC=0.0112 to 0.0247), and significant bottlenecks in almost all populations were identified, highlighting the negative impact of wetland fragmentation. The IBE model was exclusively supported for all populations and in three river basins. IBD and IBR models were supported in one river basin each. The maximum temperature of the warmest month and precipitation seasonality were the plausible environmental parameters responsible for the observed pattern of genetic diversity. Local adaptation signatures were found, with nine loci identified as outliers, four of which were gene-linked and associated with environmental variables. Based on these findings, IBE is more important than IBD and IBR in shaping the genetic structure of Z. latifolia.